1992
DOI: 10.1007/bf00011314
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrogen fixation in mixed legume/grass pastures

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
169
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(187 citation statements)
references
References 64 publications
12
169
0
6
Order By: Relevance
“…The differences were probably caused by high δ 15 N values measured in samples from these legumes in 2002/03, but it is not clear why these high values arose. (Ledgard and Steele 1992;Giller 2001). The persistently poor N 2 -fixation by CBC1 was probably also due to it being a determinate variety.…”
Section: Legume Nitrogen Accumulation and N 2 -Fixationmentioning
confidence: 99%
“…The differences were probably caused by high δ 15 N values measured in samples from these legumes in 2002/03, but it is not clear why these high values arose. (Ledgard and Steele 1992;Giller 2001). The persistently poor N 2 -fixation by CBC1 was probably also due to it being a determinate variety.…”
Section: Legume Nitrogen Accumulation and N 2 -Fixationmentioning
confidence: 99%
“…Variation in vegetation δ 15 N reflects the net effect of different processes in the local nitrogen cycle, including the rate and δ 15 N of nitrogen inputs/sources and losses, and associated fractionation effects inside the system (Högberg 1997). Such effect may result from N fixation (Ledgard and Steele 1992), ammonia volatilization or assimilation (Frank and Evans 1997;Kerley and Jarvis 1996), nitrification/denitrification (Mariotti et al 1981;Stevens and Laughlin 1998), or the plants' nitrate and ammonia uptake (Kahmen et al 2008) among others. Thus, knowledge of the δ 15 N of grassland can reveal important information on biogeochemical cycling of nitrogen in an ecosystem (Robinson 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The fixation is also regulated by a feedback mechanism involving the soil inorganic N content and competition from associated grasses (Ledgard & Steele 1992). Field studies report fixation rates from as low as 2 kg N ha 21 yr 21 up to 315 kg N ha 21 yr 21 (Vinther & Jensen 2000;Ledgard 2001;Peoples & Baldock 2001).…”
Section: Legume Nitrogen Fixationmentioning
confidence: 99%
“…Manipulating the mixture of non-legume and legume species within a pasture, for example by using appropriate grazing strategies, can also enhance legume N fixation. Transfer of fixed N within a single season from legume to non-legume via rhizodeposition is recognized around the world as a vitally important component of nutrient cycling in low-input temperate pasture systems (Boller & Nösber-ger 1987;Ledgard & Steele 1992). Controlled environment studies have demonstrated that as much as 15% of total plant N in ryegrass can originate from N exuded from companion white clover (Paynel et al 2001).…”
Section: O P T I M I Z I N G U S E E F F I C I E N C Y O F N I T Ro Gmentioning
confidence: 99%